Study of Common Bacterial and Fungal Pathogens in Children with Hematological Malignancies during Febrile Neutropenia: Single Center Egyptian Study - A. Hagag, Adel; M. Hassan, Samir; A. Elgamasy, Mohamed; K. Afifi, Ibtesam (Infectious Disorders - Drug Targets, 2016)
Background: Infection ‘is a common complication in children with hematological malignancies’ during febrile neutropenia. ‘Objective: The aim of this study was to’ evaluate common bacterial and fungal pathogens in children with hematological malignancies during febrile neutropenia in single center Egyptian study. ‘Patients and Methods: This study was carried out on 90’ children with hematological malignancies during febrile neutropenia including 54 with ALL, 27 with AML and 9 with NHL with their ages ranging from 2.5- 13 years and mean age value of 5.5 ± 3.5. Complete blood count, BM aspiration, and blood and throat cultures were done for all patients. Results: Positive bacterial growth was found in 54 cultures (30%) including 42 blood cultures and 12 throat cultures with significantly higher Gram negative bacterial growth. Staphylococcus aurous and Pseudomonas aeruginosa were the most common Gram positive and negative organisms respectively. Cefepime was the most effective antibiotic against isolated bacterial growth where 80% of Gram negative bacterial growth was sensitive to it, 20% showed intermediate response and no Gram negative Cefepime resistance was recorded. On the other hand, 62.5% of Gram positive organisms was sensitive to it, 25% showed intermediate response and Gram positive Cefepime resistance was found in 12.5%. Ampicillin sulbactam ‘was the most effective antibiotic against Gram positive’ organisms with 100% sensitivity. Positive fungal growth was found in 36 cultures (20%) including 30 throat cultures and 6 blood cultures and all fungal isolates were candida. Amphotericin was active against 100% of fungal isolates, while resistance to Fluconazole and Voriconazole was found in 25% and 33.33% respectively. Conclusions: ‘Gram negative is still more common than gram positive’ infections and fungal infection is also a common cause of fever in patients with hematological malignancies during neutropenia and must be taken in consideration in every case of febrile neutropenia.
Keywords: Febrile Neutropenia